Experimental and Theoretical Prediction of Ozone Yield by High Frequency Silent Discharge - Mochammad Facta; Hermawan Hermawan; Zainal Salam; Zolkafle Buntat (IAES Indonesia Section, 2015)
The paper uses dimensional analysis to develop atheoretical prediction of the yield of a high frequency silentdischarge ozone generator at atmospheric pressure. Theexperimental work was carried out in order to verify the viability ofthe resulting yield equation, a rectangular shaped chamber with a1.5 mm air gap was constructed. Aluminium mesh electrodes wereused with metal tape and a planar mica sheet forming a dielectricbarrier. The power supply to the chamber was from a modifiedclass E resonant power inverter. It is established that predictionsusing the yield equation match closely with data obtained from theexperimental findings